Preliminary study of the antifungal activity of fermented plant extract against Metarhizium anisopliae, Beauveria bassiana and Isaria fumosorosea - Wan Zulkifli, Wan Nur Imaan Safiya (2017)
Widespread use of chemical pesticides such as fungicides represents a potential risk to human and the environment. Therefore, the search for alternative strategies in pest control is timely to overcome this problem. One of the most important control is biological control using entomopathogenic fungi. In order to preserve entomopathogenic fungi in nature, control measures should be developed and one of the way is to use fermented plant extracts such as from curry leaves, kantan, serai wangi and watermelon. This preliminary study was carried out to evaluate the effect of fermented plant extracts (FPE) against entomopathogenic fungi. Five different FPE and three types of entomopathogenic fungi were used in the study. Results were obtained after five days incubation. Data collected were subjected to Analysis of Variance (ANOVA) and Tukey’s HSD test were used for test of mean separation. There was no significant differences in diameter of inhibition zone and percentage inhibition of diameter growth (PIDG) from all five types of FPEs. The results from the preliminary study showed that all types of FPE were not good enough in suppressing growth of entomopathogenic fungi.